2013
DOI: 10.1097/shk.0b013e318285b86d
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Abuse and the Injured Host

Abstract: Traumatic injury ranks as the number one cause of death for the under 44 year old age group and 5th leading cause of death overall (www.nationaltraumainstitute.org/home/trauma_statistics.html). Although improved resuscitation of trauma patients has dramatically reduced immediate mortality from hemorrhagic shock, long-term morbidity and mortality continue to be unacceptably high during the post-resuscitation period, particularly as a result of impaired host immune responses to subsequent challenges such as surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…Our lab and others have reported the increased level of plasma cytokines immediately after HI (34, 49). Some of these cytokines begin to appear as early as one hour after HI (34, 38, 50, 51). The initial inflammatory response is likely to be a repair process to balance cellular homeostasis, but persistent exacerbated inflammation following the initial insult contributes to organ dysfunction (5, 52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…Our lab and others have reported the increased level of plasma cytokines immediately after HI (34, 49). Some of these cytokines begin to appear as early as one hour after HI (34, 38, 50, 51). The initial inflammatory response is likely to be a repair process to balance cellular homeostasis, but persistent exacerbated inflammation following the initial insult contributes to organ dysfunction (5, 52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…Acute alcohol exposure was encountered in more than 30% of trauma patients and intoxication carried the highest risk for injury (Afshar et al, 2014; Gmel et al, 2006). In preclinical trauma studies, alcohol-induced vasodilation, diuresis, decreased cardiac output, impaired vasoreactivity, and depressed myocardial contractility negatively impacted resuscitation and worsened outcomes (Molina, Sulzer, & Whitaker, 2013). Alcohol-exposed trauma victims who survived their injuries were at increased risk for nosocomial infection and acute respiratory distress syndrome (Afshar et al, 2014; Gmel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown acute alcohol exposure resulted in suppressed pro-inflammatory cytokine release in response to an inflammatory challenge, decreased neutrophil recruitment and phagocytic function, and impaired chemotaxis (Molina et al, 2013). Most murine models focused on time points when blood alcohol was no longer present (Fuance, Gregory, & Kovacs, 1997, 1998), but even in murine models examining very early effects on immune response when blood alcohol was still present, markedly suppressed cellular immunity with inhibition of IL-6 and TNF-α production was found (Goral, Choudhry, & Kovacs, 2004; Goral & Kovacs, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Acute alcohol intoxication is a significant risk factor for traumatic injury and causes higher morbidity or mortality rates in patients with HS [6, 7]. Acute alcohol intoxication is a clinically harmful condition that commonly follows the ingestion of a large amount of alcohol [8].…”
Section: Introductionmentioning
confidence: 99%